EXPORTING LAW OR THE USE OF LEGAL TRANSPLANTS - LAURA-CRISTIANA SPATARU-NEGURA (Challenges of the Knowledge Society)
From the general theory of law, we are aware of the migration of legal concepts, practices and institutions. We believe that there are no legal system anywhere in the developed world that has not used legal transplants, that has not borrowed from another country’s laws. This paper intends to explore the concept of “legal transplants”. Why are they used? Where do they come from? Is their assimilation uncomplicated? Why are they rejected in some cases? A transplanted law should be comported with the host state in order to be accepted? Should be discussed the relationship between law and culture when contemplating a study of legal transplants? What forces propel those borrowings? However, this paper does not claim to offer definite answers to the above mentioned questions. Its goal is more modest. In understanding the phenomenon of legal transplants, we underline the fast growing importance of using the comparative research.